Robust H∞ filtering for Markovian jumping static neural networks with time-varying delays. (June 2020) - Zhao, Aodong; Zhang, Nan; Xi, Maolong; Sun, Jun; Dong, Meiyan
The problem of robust H ∞ filtering for Markovian jumping static neural networks with time-varying delays is considered in this paper. The effect of the activation function on the time delays is comprehensively considered. Based on Wirtinger inequality, a new inequality is quoted to solve the Lyapunov functions with the double-integral terms. Then, a less conservative result on the robust H ∞ filtering is obtained, which guarantees the resulting error systems stochastically stable and satisfies a prescribed H ∞ performance index. The effectiveness of the developed results is finally demonstrated by numerical examples.